Anatomy of a Discovery: M1 and M2 Macrophages - Mills, Charles Dudley (Frontiers in Immunology, 2015)
M1 and M2 macrophage-type responses kill or repair in vivo. The unique ability of macrophages to make these polar opposite type of responses provides primary host protection and maintains tissue homeostasis throughout the animal kingdom. In humans and other higher animals M1 and M2-type macrophage responses also initiate and direct T cells/adaptive immunity to provide additional protection such as Th1 (cytotoxic) or Th2 (antibody-mediated) type responses. Hence, macrophages were renamed M1 and M2 to indicate the central role of macrophages/innate immunity in immune systems. These findings indicate that the long held notion that adaptive immunity controls innate immunity was backward: a sea change in understanding how immune responses occur. The clinical impact of M1/kill and M2/repair responses is immense playing pivotal roles in curing (or causing) many diseases including infections, cancer, autoimmunity and atherosclerosis. How M1/M2 came to be is an interesting story that, like life, involved Direction, Determination, Discouragement and Discovery.